Penerapan Lesson Study melalui Project Based Learning (PjBL) Pada Mata Pelajaran IPA SMP - Huda, Muhammad Khomarul; Sinaga, Yuliana K. B.; Saragih, Sarlina (Journal of Natural Sciences, 2024)
This article discusses the implementation and application of "Lesson Study based on Project Based Learning" in science subjects in junior high schools. The aim of this research is to explain the implementation of lesson study based on Project Based Learning. The research method used is the literature study method. The research results show that the application of lesson study based on project based learning can improve teacher professionalism and pedagogical skills, the quality of education in schools, improve learning outcomes, student activities, creative thinking skills, and increase information literacy in the 21st century.